Legal Certainty of Fulfilment of Registered Trademark Rights Owned by the Company for the Similarity of Trademarks in Principal - Anugrah Syahrial; Alfalah Naufal Yufianda; Hafiyyan Daffa Muhammad; Giovanni Akmal Firdausy (Dinasti Research, 2024)
The main function of a brand is to differentiate a company's products. A brand can create a reputation regarding quality, quantity and distinctiveness that is only owned by the party attached to the brand rights which are exclusively owned by the brand holder. However, it cannot be denied that later it was discovered that there were two brands that were fundamentally similar, causing disputes. The aim of this research is to explore the legal certainty of fulfilling a company's registered trademark rights for the existence of substantially similar brands by examining the concept of the element of